A Robust Mag/INS-Based Orientation Estimation Algorithm for Measurement While Drilling - Yang, Jinxian; Yang, Chuang; Jiang, Jinbao (IEEE sensors journal, 2017)
In order to obtain an optimal orientation of the bottom hole assembly while drilling, a novel robust Mag/INS-based orientation estimation algorithm, designed to support a magnetic/ inertial-based measurement while drilling (MWD) surveying system, is proposed and assessed. First, a magnetic/inertial-based MWD surveying system has been designed by employing triaxial accelerometers, triaxial magnetometers, and triaxial gyroscopes. Second, in the Kalman filter framework the orientation-dependent components, i.e., the Earth's gravity field and the Earth's magnetic field, are decoupled from the vibration and magnetic disturbances respectively based on Coriolis transfer equation. Third, in the federal Kalman filter framework, the extracted gravity and magnetic field measurements are robustly fused together with angular velocity readings from the gyroscopes by employing the failure detection and inter(FDI) technique. Semi-physical simulation and actual drilling experiments show that the proposed novel robust Mag/INS-based orientation algorithm adapts well to the severe conditions of the drilling environment and can effectively improve measurement precision and reduce errors produced by drillstring vibration and magnetic disturbances.